Evaluación de un Protocolo de IATF (inseminación artificial a tiempo fijo) con gonadorelinas previo a la inseminación en Ganado Bovino en el sector de Tanicuchi Hacienda “Las Lomas” en el período agosto 2018 – febrero 2019. - Vinueza Lozada, Jaime Geovanni (2019)
The research project was carried out in the hacienda "LAS LOMAS" located in the Province of Cotopaxi, Canton Latacunga, in the Parish of Tanicuchi; which was carried out in order to evaluate a Fixed Time Artificial Insemination Protocol "IATF", using as main instruments the intravaginal implants with progesterone "CIDR" applied on day zero plus the administration of 2 ml of estradiol benzoate IM, On the seventh day the intravaginal implants were removed and 2 ml of Estrumate (F2 &) was applied, which is a prostaglandin, on day eight, 1ml of Estradiol Benzoate BE was applied, on the 9th the devices were removed, and we applied 3ml of Gonadorelins "Conceptal" 15 to 30 minutes before the AI, and finally it was inserted on day 10 or it is calculated between 54 to 58 hours after implant removal, for which twenty-seven (27) vaconas with the same characteristics were selected in terms of body condition, diet and management conditions. The objective of the research was to evaluate the animals that are pregnant, that return to natural estrus and the cyclicity of the post IATF protocol. The vaconas are of Holstein breed, ages between 15 and 18 months and an ovarian corpus luteum condition for all. Finally, on the 45th day after the completion of the treatment, a gynecological check-up was performed on all the vaconas to know the presence or absence of pregnancy. The characteristics of the animals showing estrus, the pregnancy and the return of the estrous cycle were evaluated. It was verified that within the group under treatment there were 17 vaconas in gestation n, 10 who returned to estrus after the I.A. of a total of 27 vaconas after the protocol was made. In the cost-benefit analysis, the economic feasibility of the treatment was determined, since 63% of pregnant animals and 37% of animals that did not reach their pregnant status were obtained.